ANALYSIS OF THE IMPLEMENTATION OF TRANSFORMATIONAL LEADERSHIP AND DIGITAL TRANSFORMATION IN ORGANIZATIONAL EFFECTIVENESS - Farhan Akbar Salim Rangkuti; Marlon Sihombing (Awatara Publisher, 2024)
The Post Office is a government organization that facilitates the public with communication tools such as mail and parcel delivery services. The role of the Post Office in the digital era and the implementation of transformational leadership at the Kisaran Post Office. The Post Office originally served mail and parcel delivery, but it has now expanded to provide services such as Western Union and utility bill payments. This research aims to understand the implementation of transformational leadership by executive managers at the Kisaran Post Office and the impact of digital transformation on organizational effectiveness. This research uses a descriptive qualitative method with purposive sampling techniques and involves three informants as a source of information. Primary data is obtained through structured interviews with informants, while secondary data comes from literature reviews, observations, and field documents. Data analysis is conducted continuously until the data is fully collected. The research results show that: (1) Executive managers at the Kisaran Post Office do not fully implement transformational leadership but use a combination of leadership styles. (2) The implementation of digital transformation at the Kisaran Post Office is going well but has some shortcomings. In conclusion, this research identifies that the Kisaran Post Office has not fully implemented transformational leadership, and there is still room to improve the implementation of digital transformation to enhance organizational effectiveness.